(untitled) (The Geographic Base, 2023)
Nepal is located in a seismically active region with a long history of devastating earthquakes. Likewise, several earthquake incidents have been recorded in the Western Nepal The study aims to illustrate the earthquake scenario and analyze the socio-economic impacts in the Sudur Pashchim and Karnali Provinces. A mixed-method research approach was used to meet the objectives of the study. Two hundred households were surveyed and field observations were accomplished for primary data in the most affected areas. Moreover, secondary data were collected from official reports, online portals, news articles, and literature reviews. ArcGIS 10.8.2, GPS, and Excel sheets were used to analyze the data. The study found that about 293 earthquakes incidents with 4 to 6.6 magnitudes hit the region from 1994-2023. Bajhang, Bajura, Humla, and Darchula districts experienced more strokes than others. However, Dadeldhura, Kanchanpur, Surkhet, Dolpa, Kailali, Salyan, and Baitadi districts experienced minimal strokes. The earthquakes affected 292 casualties, 332 injuries, and 3880 families. Besides, private houses were partially and fully damaged more than government houses in the study area. Also, earthquakes impact socially and psychologically which could cause short or long-term trauma. During the disaster, Earthquake survivors need proper healthcare, shelter, food, clothes, security, and other basic needs. So, they hope with the government and other helping hands. Thus, stakeholders related to disasters, should have enough preparedness and organize awareness programs in the school to community level which can help to mitigate the problems after the disaster.